1998
DOI: 10.1042/bj3310767
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of activation-induced apoptosis of thymocytes by all-trans- and 9-cis-retinoic acid is mediated via retinoic acid receptor α

Abstract: Thymocytes can be induced to undergo apoptotic cell death by activation through the T-cell receptor (TCR). This process requires macromolecular synthesis and has been shown to be inhibited by retinoic acids (RAs). Two groups of nuclear receptors for RAs have been identified: retinoic acid receptors (RARs) and retinoid X receptors (RXRs). All-trans-RA is the high-affinity ligand for RARs, and 9-cis-RA additionally binds to RXRs with high affinity. Because 9-cis-RA is much more potent in inhibiting TCR-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 44 publications
6
41
0
1
Order By: Relevance
“…First, retinoids are known to regulate apoptosis in T lymphocytes, thymocytes, and T lymphoma cells (7,21,44). Second, in addition to promoting Th2 development, treatment with the RXR agonist AGN194204 during primary antigenic stimulation reproducibly caused a greater accumulation of viable cells after 1 wk of culture than did treatment with the vehicle control.…”
Section: Dna Microarray Analysis Following Primary Stimulation Of Naimentioning
confidence: 99%
“…First, retinoids are known to regulate apoptosis in T lymphocytes, thymocytes, and T lymphoma cells (7,21,44). Second, in addition to promoting Th2 development, treatment with the RXR agonist AGN194204 during primary antigenic stimulation reproducibly caused a greater accumulation of viable cells after 1 wk of culture than did treatment with the vehicle control.…”
Section: Dna Microarray Analysis Following Primary Stimulation Of Naimentioning
confidence: 99%
“…Selective ligation of RAR § , on the other hand, inhibited negative selection [15,27] or activationinduced apoptosis of T cell hybridomas [13] and T lymphocytes from HIV-infected individuals [14,28]. It was also demonstrated that selective ligation of RAR § and RAR + affects the function and the expression of the nur77 transcription factor, an apoptosis-linked protein, respectively [13,15].…”
Section: Discussionmentioning
confidence: 97%
“…After the discovery of nuclear retinoid receptors and their ligands, and the demonstration of the expression of RAR § and RAR + in T cells [12,24], suggestions have been made that the active metabolites of vitamin A that mediate its effects on the immune system are the RA, including all-trans RA and 9-cis RA [25]. Indeed, RA were shown to promote T cell proliferation [24], and to affect apoptosis of T cells at various stages of their differentiation [12][13][14][15][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…DNA fragmentation was analysed as described previously with some modification (Szondy et al, 1998). Briefly, thymus and spleen tissues from the mice were gently glassground to dissociate the cells, and then suspended in cold Hanks' balanced salt solution (HBSS), which was then gently passed through a stainless steel mesh to obtain single-cell suspensions (thymocytes and splenocytes).…”
Section: Methodsmentioning
confidence: 99%